Bathing pool at Point Baleine, Trinidad - (:unkn) unknown (My University, 2011)
The postcard show a diver in mid flight at Point Baleine on Gasparee Island.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Divers--Trinidad and Tobago; Gaspar Grande; Islands--Trinidad and Tobago